46,XY ovotesticular disorders of sex development: A therapeutic challenge - Maria-Grazia Scarpa; Massimo Di Grazia; Gianluca Tornese (MDPI AG, 2017)
46,XY ovotesticular disorder of sex development is extremely rare and indicates the presence of both testis and ovary in the same patient. Gender assignment in newborns represents a therapeutic challenge. We describe and comment on our multidisciplinary approach, ten years after the Chicago consensus meeting on disorder of sex development.